Teori pemprosesan maklumat : penyelesaian masalah dan membuat keputusan dalam domain penilaian prestasi SSB - Che Mohd. Hazidi, Bin Che Wil (1998)
This study looks at decision making and problem solving process in evaluation and selection of candidate for the award of 'melintang' category according to 'SSB' scheme. The study investigates how the generative knowledge, structure process and conceptual operations of cognition and the use of the lines of reasoning mechanisms are related to the problem solving process of selecting candidates for the award of 'melintang' category according to the SSB scheme by experienced performance appraisers and "Panel Pergerakan Gaji" (PPG) pass and less experienced performance appraisers and non of PPG panel. subjects of this study consist of 2 experienced performance appraisers and PPG panel and less experienced performance appraisers and PPG Panel. Experienced subject is a Head of Department in Teacher Training College and a Principal in Secondary school.